Impact of feeding level and multi-nutrient blocks with polyherbals on weight changes and greenhouse gas emissions in lambs - Sánchez-López, Nallely; Mendoza-Martinez, Germán David; de la Torre-Hernández, María Eugenia; Hernández-García, Pedro Abel; Díaz-Galván, Cesar; Ortega-Navarro, Gilberto Carlos; Fuentes Ponce, Mariela; Leal Gonzalez, Abel Jaime; Lopez-Ridaura, Santiago; Van Loon, Jelle (MDPI, 2025)
In small-scale livestock production systems, low-quality diets constrain animal performance and increase enteric emissions, but both these impacts can be remediated using optimized feeding strategies. An experiment was conducted with lambs fed at two levels-maintenance (MN) and growth (GR)-using multi-nutrient blocks formulated with different concentrations of polyherbal nutraceuticals to compare the lambs' reactions in terms of their productive performance and estimated enteric methane emissions. Thirty-two lambs were fed at two feeding levels-(a) maintenance (MN) at 9% CP and 1.85 Mcal ME/kg DM and (b) growth (GR) at 13.24% CP and 2.15 Mcal ME/kg DM)-and did or did not have access to MBs with different polyherbal percentages (BioCholine (R), OptiLysine (R), and OptiMethione (R) (0:0:0, 3:0:0, 3:0.75:0.25)). No interactions between the feeding level and supplementation were detected. Lambs fed at the MN level showed lower productive indicators (p < 0.001) than those fed at the GR level, with a lower dry matter intake (DMI, 512 vs. 1009 g/d), MB consumption (61 vs. 84 g/d), and daily weight gain (26 vs. 187 g/d), resulting in lower enteric methane emissions (8.74 vs. 18.18 g CH4 /d) and a lower emission intensity (15.25 vs. 16.55 CH4 g/kg DM). Supplementation with MBs improved the average daily weight gain (ADG) (p < 0.001) at the GR level, but no differences were detected at the MN level. However, lambs in the control group lost weight (-20 g/d) and those supplemented gained weight (g/d), with increases of 49 (0:0:0), 25 (3:0:0), and 52 (3:0.75:0.25). The highest ADG for lambs in the GR group was observed with MBs containing all three polyherbals (215a, 3:0.75:0.25), an intermediate ADG was seen with MBs without herbals or with Biocholine (200.75ab, 0:0:0; 198ab, 3:0:0), and the lowest ADG was observed with no MBs (134c g/d). The use of MBs reduces the time to reach market weight by 265 days, resulting in a 50% reduction in the enteric methane emissions per product (animal by animal), making multi-nutrient blocks a viable option to improve production indicators and reduce enteric methane emissions.